El modelo costo - volumen - utilidad y su mpacto en la toma de decisiones de la empresa Vitalia Health Care & Medical Services S.A.C. en Trujillo 2016 - Gonzales Chamay, Cristian Alexander (2017)
The present research was elaborated with the purpose of informing about the Cost - Volume - Utility Model and its impact on the decision - making of the company Vitalia Health Care & Medical Services SAC, based on general cost topics, Balance, and decision making. The Cost - Volume - Profit Model nowadays becomes a contemporary and important tool since the implications they have, both in the short and the long term, are very positive for companies. In this way the Cost - Volume - Profit Model becomes an effective trend for results planning and decision making. This report was developed with a descriptiveapplication comparison design, the methods applied were: method of analysis - synthesis and the hermeneutic method; And for the collection of information we used both documentary analysis and observation. In the documentary analysis, we can point out that a costing, a break - even point and the application of the Cost - Volume - Profit Model are topics valued for the development of good management of some changes and effective decision making. After this research we can conclude that the Cost - Volume - Profit Model has a positive influences on the decision making of Vitalia Health Care & Medical Services S.A.C.